Communications and relationships between patient and nurse in Intensive Care Unit: knowledge, knowledge of the work, knowledge of the emotional state - Foà, Chiara; Cavalli, Lisa; Maltoni, Alessia; Tosello, Nicoletta; Sangilles, Chiara; Maron, Ilaria; Borghini, Marina; Artioli, Giovanna (Acta Biomedica Atenei Parmensis, 2016)
Background and aim: In an Intensive Care Unit (ICU) the communication between nurse and patient, the core of the care, is often hindered by patient’s cognitive alterations and critical situation, by devices employed for the mechanical ventilation, and by the clinical and care-giving setting. How to overcome these barriers? How is the relational and communicative approach between nurse and patient unable to express him or herself to be managed? The available literature reveals that studies on communication with difficult patients, such as those treated in ICU are currently scarce. Method: The present research offers a contribution in this respect, through fact-finding about the knowledge acquired by professional studies or work experiences, the personal and institutional techniques implemented in regards to communication (knowledge of the work), the relational behaviours and the emotional experience with patients (knowledge of the emotional state) of nurses working in the Intensive Care Units. A semi-structured interview have been designed and submitted to 30 nurses working in fourteen Highly Specialized Centres (HUB) in Emilia Romagna, Italy. Two nurses with different years of experience in the field have been chosen for each Operating Unit. Results: According to the interviewees paraverbal communication is the most common way to communicate with patients: different strategies are employed such as facial expression or lip movement. In any case, the nurse has the task to choose the most suitable technique according to his or her experiences, his or her knowledge and the patient him or herself. The results claim that lack of specific training on communicative aspects of care, should be combined with an attitude of being prone to listening to and understanding the needs of the patient and of his or her family as well. Conclusion: The interviewees declare they have a solid preparation in the bio-clinical aspect of care, but both new hired nurses and experts affirm that they need a specific training in relational and communicative aspects, proving its importance.